Endohedral metallofullerenes in self-assembled monolayers - Gimenez-Lopez, M; Gardener, J; Shaw, A; Iwasiewicz-Wabnig, A; Porfyrakis, K; Balmer, C; Dantelle, G; Hadjipanayi, M; Crossley, A; Champness, N; Castell, MR; Briggs, G; et al. (2010)
A method has been developed for the attachment of a dithiolane group to endohedral metallofullerenes via a 1,3-dipolar cycloaddition reaction. This sulfur-containing functional group serves as an anchor, enabling efficient immobilisation of endohedral fullerenes on Au(111) surfaces at room temperature, directly from the solution phase. The functionalised fullerenes form disordered monolayers that exhibit no long-range ordering, which is attributed to both the strong bonding of the dithiolane anchor to the surface and to the conformational flexibility of the functional group. Endohedral fullerenes Er3N@C80 and Sc3N@C80 have been used as models for functionalisation and subsequent surface deposition. Their chemical reactivity towards dithiolane functionalisation and their surface behaviour have been compared to that of C60. The endohedral fullerenes appear to be significantly less reactive towards the functionalisation than C60, however they bind in a similar manner to a gold surface as their dithiolane terminated C60 counterparts. The optical activity of Er3N@C80 molecules is preserved after attachment of the functional group. We report a splitting of the endohedral Er3+ emission lines due to the reduction in symmetry of the functionalised fullerene cage, as compared to the highly symmetrical icosahedral C80 cage of pristine Er3N@C80.